The Effects of Error Frequency and Accounting Knowledge on Error Diagnosis in Analytical Review. - Nelson, Mark W. (The Accounting Review, 1993)
The performance of audit tasks has been modeled as a function of the auditor's ability, knowledge and experiences (Libby 1993). Thus, an important aspect of assigning audit tasks is identifying the levels of knowledge and types of experience an auditor must have to achieve a sufficiently high level of performance (Abdolmohammadi and Wright 1987). An objective of the current study is to determine whether auditors' knowledge of basic accounting principles and error frequencies improves over the course of their early careers so as to enhance performance of a common analytical procedure, ratio analysis. Research in psychology suggests that two characteristics of a task (say, analytical procedures) could diminish the accuracy with which auditors learn error frequencies from experience and apply their knowledge to a task. First, auditors' memories of financial statement errors are encoded while they perform other information-processing activities. These competing task demands could use enough of an auditor's information-processing capacity to diminish both the accuracy with which memory traces of errors are encoded and the accuracy of their knowledge of error frequency (Naveh-Benjamin and Jonides 1986). Second, auditors must consider a variety of evidence when performing analytical procedures. In diagnostic tasks like ratio analysis, inordinate attention is given to evidence that is highly diagnostic of low-frequency events, causing an "inverse base rate effect" in which auditors consider such events as more likely (Medin and Edelson 1988). Assessing the extent to which either of these characteristics of the analytical procedures context prevents auditors from learning and applying error frequency knowledge is a second objective of this study. To test hypotheses about these objectives, an experiment is conducted in which experienced auditors, accounting students, and nonaccounting students learn the frequencies of financial statement errors through their experience in solving a series of problems using ratio analysis. Subjects are then tested for their accuracy in using frequency information by having them diagnose novel combinations of the same evidence. Other subjects perform similar tasks for an abstract medical diagnosis to provide a benchmark for comparison. The results indicate that differences in accounting knowledge influenced the subjects' performance of ratio analysis, and that neither potential source of inaccurate learning of event frequency knowledge holds in this setting. That is, subjects learned frequencies in the presence of competing task demands, and the inverse-base rate effect was not observed. These results suggest that experienced, but not novice, auditors use both their superior knowledge of accounting and of error frequencies learned through experience. Another implication is that the performance of novice auditors may be improved by increasing their knowledge of basic accounting principles and error frequencies.